Study of Antifungal Activity of Different Concentrations of Clove Oil against Corynespora cassiicola by Poisoned Food Technique (International Journal of Food and Nutritional Sciences, 2023)
Fungal infections pose a significant threat to human health, agriculture, and the environment. The emergence of drug-resistant strains has further emphasized the need for novel antifungal agents. The present study aims to investigates the antifungal activity of clove oil, a natural product derived from Syzygium aromaticum, against Fusarium graminearum isolated from ridge gourd (Luffa acutangula) using the Poisoned Food Technique. Different concentrations of clove oil were tested to determine their inhibitory effects on Fusarium graminearum growth. The results demonstrated that clove oil exhibits promising antifungal properties, inhibiting the growth of Fusarium graminearum in a dose-dependent manner. These findings contribute to our understanding of the potential use of clove oil as a natural alternative to conventional antifungal agents.